Analysis of the selected national eHealth strategies and a proposal of the conception for the Czech Republic - Debnárová, Barbora; Voříšek, Jiří, 1950-; Quirchmayr, Gerald; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2016)
This diploma thesis is dedicated to the analysis of eHealth strategies of the German speaking countries and to the proposal of a conception for the Czech Republic. The first part is dedicated to theory. At the beginning, it provides a brief review of the literature which has already been written about this topic. Further, it deals with the topic and definition of eHealth in general, its history, applications, benefits, and the way how eHealth is approached by the European Union. The second chapter provides analysis of eHealth and its technologies in Austria, Germany and Switzerland. At the end of the chapter, the comparison of the current states of eHealth in these countries is conducted. The third chapter deals with the current state of eHealth in the Czech Republic. The last chapter is dedicated to the proposal of the conception for the Czech Republic.
Vedoucí práce: Jiří Voříšek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses